Retrospective Study of Suicide Among Children and Young Adults - Mishra, Navin; Shrestha, Devendra; Poudyal, Rakesh Babu; Mishra, Pravin (Journal of Nepal Paediatric Society, 2013)
Introduction: The prevalence of suicide has been increasing globally in all age groups. There is dearth of literature on suicide among younger patients from developing country. The objective of this study was to find out the prevalence and cause of suicide as well as to identify the vulnerable groups of children and young adults to suicide. Materials and Methods: This is a retrospective observational study. Data was collected from the Police Head Quarters in Kathmandu and included all completed suicide cases of less than twenty one years of age from January 2005 to December 2009. Results: There were a total of 2172 documented cases of completed suicide in the age group between 4 to 21 years. The majority were female and belonged to the adolescent age group. The incidence of suicide showed an increasing trend within the five years of the study. A monthly breakdown of the cases revealed that the incidence of suicide was lowest in January and February and peaked from April to October. Hanging was the most common mode of suicide followed by poisoning and drowning. The reason for suicide could be ascertained only among 25.5 % of cases. Domestic violence (35%), mental illness (24%), failure in academic achievement (15.8%) and end of a romantic relationship (8.7%) were found to be common causes of committing suicide. Of the 87 cases found who committed suicide because of academic failure 46.6% were at a grade ten level. Conclusions: Suicide in children and young adults in Nepal appears to be a concealed but serious problem requiring immediate attention and systematic efforts. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7512 J Nepal Paediatr Soc. 2013; 33(2):110-116